The Causal Role of Mitochondrial Dynamics in Regulating Innate Immunity in Diabetes - Chang, Yen-Hsiang; Lin, Hung-Yu; Shen, Feng-Chih; Su, Yu-Jih; Chuang, Jiin-Haur; Lin, Tsu-Kung; Liou, Chia-Wei; Lin, Ching-Yi; Weng, Shao-Wen; Wang, Pei-Wen (Frontiers in Endocrinology, 2020)
Background There is considerable evidence that chronic low-grade inflammation caused by activation of the innate immune system plays an essential role in the pathogenesis of type 2 diabetes (T2D). Using trans-mitochondrial cybrid cell model, we have demonstrated the independent role of mitochondria in the pathogenesis of insulin resistance (IR) and pro-inflammation in cybrid cells harboring diabetes-susceptible mitochondrial haplogroup B4. Cybrid B4 showed a more fragmented mitochondrial network and a low expression of fusion-related molecules. We also discovered the causal role of mitochondrial dynamics (mtDYN) proteins in regulating IR in this model, and the bidirectional interaction between mtDYN and mitochondrial oxidative stress is considered etiologically important. Herein, we further investigated whether mtDYN may be a bridge between nutrient excess and chronic inflammation in T2D. Methods Trans-mitochondrial cybrids derived from the 143B osteosarcoma cell line were cultured in medium containing glucose (25 mM) with or without saturated fatty acid (0.25 mM BSA-conjugated palmitate), and the expression of innate immunity-inflammasome components was compared between cybrid B4 (the major diabetes-susceptible haplogroup in Chinese population) and cybrid D4 (the major diabetes-resistant haplogroup in Chinese population). Manipulating mtDYN proteins in cybrid B4 and pharmacologically inhibiting mitochondrial fission by the Drp1 inhibitor, mdivi-1, and metformin were used to investigate the causal relationship between mtDYN and inflammation caused by nutrient excess. Results Under nutrient excess with high fatty acid, cybrid B4 presented increased mitochondrial pro-fission profiles, enhanced chronic inflammation markers (RIG-I, MDA5, MAVS) and inflammasome (NLRP3, Caspase-1, IL-1β), whereas the level in cybrid D4 were not or less significantly altered. In cybrid B4 under nutrient excess, overexpression of fusion proteins (MFN1 or MFN2) significantly diminished expressions of innate immunity-inflammasome components, while knockdown had less significant effect. In contrast, knockdown of fission proteins (DRP1 or FIS1) significantly diminished expression of innate immunity-inflammasome components, while overexpression had less significant effect. Drp1 inhibitor mdivi-1 and metformin, also inhibited mitochondrial fission and attenuated the pro-inflammation expression. Conclusion Our results discovered the causal role of pro-fusion mtDYN in regulating nutrient excess-induced chronic inflammation in a diabetes-susceptible cell model. Direct intervention to reverse pro-fission in mtDYN may provide a therapeutic strategy for T2D.